Soybean response to starter nitrogen and Bradyrhizobium inoculation on a Cerrado oxisol under no-tillage and conventional tillage systems - Mendes,I. C. (2003)
In Brazil, Bradyrhizobium inoculation has successfully replaced the use of N fertilizer on soybean [Glycine max (L) Merr.] crops. However, with the expansion of no-tillage cropping systems in the Cerrados region, the idea that it is necessary to use small N rates at the sowing to overcome problems related with N immobilization has become widespread, mainly when soybean is cultivated after a non-legume crop. In this study we examined soybean response to small rates of N fertilizer under no-tillage (NT) and conventional tillage (CT) systems. Four experiments (a completely randomized block with five replicates) were carried out in a red yellow oxisol, during the periods of 1998/1999 and 1999/ 2000, under NT and CT. The treatments consisted of four urea rates (0, 20, 30 and 40 kg ha-1 N). All treatments were inoculated with Bradyrhizobium japonicum strains SEMIA 5080 and SEMIA 5079, in the proportion 1 kg of peat inoculant (1,5 x 10(9) cells g-1) per 50 kg of seeds. In both experiments, soybean was cultivated after corn and the N fertilizer was band applied at sowing. In all experiments, N rates promoted reductions of up to 50 % in the nodule number at 15 days after the emergence. Regardless of the management system, these reductions disappeared at the flowering stage and there was no effect of N rates on either the number and dry weight of nodules or on soybean yields. Therefore, in the Brazilian Cerrados, when an efficient symbiosis is established, it is not necessary to apply starter N rates on soybean, even when cultivated under notillage systems.